Hubungan Pengetahuan Ibu tentang Teknik Menyusui dengan Bendungan ASI di PMB Pratiwi Agustian Kulon Progo - Riskiana Rahma Syifa; Isne Susanti; Eka Oktavia (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2025)
Infant mortality rates (IMR) at the global and national levels occur mostly during the neonatal period. One way to reduce infant mortality is to provide the best food, namely breast milk. The breastfeeding process can be hampered due to several problems, one of which is the occurrence of breast milk dams. The purpose of the study was to determine the relationship between mothers' knowledge about breastfeeding techniques and breast milk dams at PMB Pratiwi Agustian. The research method used was a quantitative analytic study with a cross sectional design. The research sample was 28 respondents using total sampling technique. Data were collected through questionnaires and analyzed using the chi-square test. The results showed that the majority of breastfeeding mothers with good knowledge of breastfeeding techniques did not experience breast milk dams as many as 5 people (71.4%), 13 people (76.5%) did not experience breast milk dams in the moderate category, and 4 people (100.0%) experienced breast milk dams in the poor category. Correlation analysis showed that there was a relationship between knowledge of breastfeeding techniques and breast milk dams in nursing mothers at PMB Pratiwi Agustian with a significant value of p = 0.015. Lack of knowledge about proper breastfeeding techniques can increase the risk of breast milk dams in mothers. Therefore, improving mothers' knowledge and skills in breastfeeding through proper education and counseling is crucial to prevent or reduce the incidence of breast milk dams.